2018
DOI: 10.2478/amcs-2018-0053
|View full text |Cite
|
Sign up to set email alerts
|

From Exhaustive Vacation Queues to Preemptive Priority Queues with General Interarrival Times

Abstract: We consider the discrete-time G/GI/1 queueing system with multiple exhaustive vacations. By a transform approach, we obtain an expression for the probability generating function of the waiting time of customers in such a system. We then show that the results can be used to assess the performance of G/GI/1 queueing systems with server breakdowns as well as that of the low-priority queue of a preemptive M X +G/GI/1 priority queueing system. By calculating service completion times of low-priority customers, vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In this setting class, we can restrict our search for an optimal policy to the class of stationary policies (Fiems & De Vuyst, 2018). A stationary policy assigns actions based only on the current state of the system, regardless of the point in time at which the decision is being made.…”
Section: Model Formulationmentioning
confidence: 99%
“…In this setting class, we can restrict our search for an optimal policy to the class of stationary policies (Fiems & De Vuyst, 2018). A stationary policy assigns actions based only on the current state of the system, regardless of the point in time at which the decision is being made.…”
Section: Model Formulationmentioning
confidence: 99%
“…These additional assumptions make research more complicated but let us successfully use introduced models in practice. Some aspects of customers' non-homogeneity have recently appeared in many works of researchers from different countries [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the preemptive repeat priority policy has been adopted for the prioritization of handoff calls over new calls. An overview of research works on the preemptive repeat PQM can be found in the articles (refer, [1,6,9,13], etc.). In these studies, challenges arising due to the consideration of the preemptive repeat policy have been emphasized.…”
Section: Introductionmentioning
confidence: 99%